From terror to pride: Supporting faculty through a blended learning community of transformation during the COVID-19 pandemic - Adam Barger; Katalin Wargo; Kelly Leffel; Mark Hofer (To Improve the Academy)
The COVID-19 pandemic and the shift to remote, blended, and online teaching and learning presented universities around the world with myriad challenges. This rapid shift into uncharted territory, however, also created an opportunity for faculty developers to lead exploration of new pedagogies, challenging teaching assumptions. In this article, we share the story of how a center for teaching and learning led the shift to remote and blended learning through a community of transformation (Kezar et al., 2018). We share results from a survey of faculty following multiple professional development opportunities and explore themes that emerged from interviews with six instructors representing a range of disciplines and experience in remote and blended teaching. We conclude by offering our design elements to consider when pursuing faculty development as a potentially transformative learning experience (Mezirow, 1991).